Biochemical characterization of cholinesterases in Enchytraeus albidus and assessment of in vivo and in vitro effects of different soil properties, copper and phenmedipham - Howcroft, CF
Enchytraeus albidus are important organisms of the soil biocenosis, used as standard test species in environmental risk assessment. The inhibition of cholinesterases (ChE) activity of several species has been widely used to assess the exposure and effects of anti-cholinesterase environmental contaminants. Several studies have shown the association between ChE activity inhibition and adverse effects on behaviour and survival. Extensive studies addressing survival and behavioural endpoints, as well as other biomarkers, have been done in E. albidus with different types of soil contaminants. The main objectives of this study were: (1) to characterize biochemically the ChE present in the soluble post-mitochondrial fraction of E. albidus whole body homogenates, using different substrates and selective inhibitors; (2) to assess the in vivo effects of copper, phenmedipham and different soil properties (pH, organic matter, clay) on the ChE activity; (3) to assess the in vitro effects of copper and phenmedipham on the ChE activity. The results suggest the presence of one ChE in the soluble post-mitochondrial fraction of E. albidus whole body homogenates, which displays properties of both acetylcholinesterase and pseudocholinesterase considering the typical mammalian enzymes. It is also shown that ChE activity is not inhibited by exposure to different soil properties and that copper and phenmedipham inhibited ChE activity both in in vivo and in in vitro conditions and therefore ChE inhibition seems to be a robust biomarker for this herbicide and this heavy metal. This study showed that ChE activity in E. albidus might be correlated to previously determined higher level effects like survival and reproduction, as well as avoidance behaviour.